Study on Economic-Ecological Resilience Measurement and Improvement Strategy of Yunnan Ethnic Regions - Li, Ruiliang; Li, Yan; Shen, Jie; Fu, Chao; Xia, Chunhong; Li, Zhangfeixue (European Publisher, 2019)
Nowadays, the ecological environment has been seriously damaged due to the continuous development of social economy and the rapid advancement of urbanization. The construction of ecological civilization has become the focus of common concern of all sectors of society. Yunnan ethnic minority areas are mostly distributed in ecological fragile areas, facing the threat of natural disasters, such as earthquakes and mudslides, and their economic development is also relatively backward. Therefore, using the coordinated development model, this paper takes 8 ethnic minority areas in Yunnan Province as the research object to measure it’s economic and ecological resilience and the coordination between them. Results prove that: First, the economic resilience and ecological resilience of Yunnan ethnic areas have significantly improved, but the level is still to be improved; Second, there is a huge gap of economic and ecological resilience among regions; Third, the coordinated degree of regional economic and ecological resilience showed a good trend of stable, and constantly coordinated development. Finally, this paper proposes specific strategies to promote the resilience of ethnic regions from the perspective of economy, ecology and the coordination relationship between them, in order to achieve a “win-win” economic development and ecological security in ethnic areas.